2020
DOI: 10.1051/e3sconf/202018503050
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Antilipidemic Activity of Artemisia Annua Aqueous Extract

Abstract: Artemisia annua is an annual herb, which is a traditional Chinese medicine in China. The high water soluble artemisinin derivative extracted from Artemisia annua is Artemisia annua water extract. In this experiment, the modeling method is used, and the Artemisia annua water extract is used alone or in combination with other lipid-lowering drugs. Finally, the results showed that the effect of the combination of drugs was better than that of Artemisia annua water extract alone, and the effect of the drug ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This suggests that further extraction of biologically active components of A. annua would yield more meaningful effects. Consistent with this, it was found that the water extract of A. annua has strong immune, antioxidant (lesser mulberry snout moth ( Glyphodes pyloalis )), antilipidemic (rats), antibacterial, and antiviral activity (human cervical cancer cells)[ 11 , 12 , 13 ]. Notably, using water as a solvent to extract bioactive ingredients results in high yield and high content of each bioactive ingredient[ 14 ], with relatively low cost.…”
Section: Introductionmentioning
confidence: 71%
“…This suggests that further extraction of biologically active components of A. annua would yield more meaningful effects. Consistent with this, it was found that the water extract of A. annua has strong immune, antioxidant (lesser mulberry snout moth ( Glyphodes pyloalis )), antilipidemic (rats), antibacterial, and antiviral activity (human cervical cancer cells)[ 11 , 12 , 13 ]. Notably, using water as a solvent to extract bioactive ingredients results in high yield and high content of each bioactive ingredient[ 14 ], with relatively low cost.…”
Section: Introductionmentioning
confidence: 71%